Predictors of malignancies and overall mortality in Japanese patients with biopsy‐proven non‐alcoholic fatty liver disease. Issue 7 (30th September 2014) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Taketani, Hiroyoshi; Kanemasa, Kazuyuki; Ishiba, Hiroshi; Okajima, Akira; Nishimura, Takeshi; Yamaguchi, Kanji; Moriguchi, Michihisa; Mitsuyoshi, Hironori; Yasui, Kohichiroh; et al.
<x xml:space="preserve">Abstract</x> Aim Some patients with non‐alcoholic fatty liver disease (NAFLD) develop hepatocellular carcinoma (HCC) and have higher mortality than others. The evidence causally linking NAFLD to extrahepatic malignancies is scarce. Our aim was to determine the incidence of and risk factors for HCC, extrahepatic cancer and mortality in Japanese patients with biopsy‐proven NAFLD. Methods This retrospective cohort study analyzed outcomes including onset of malignant tumors and death in 312 patients with NAFLD diagnosed by liver biopsy. Results Of 312 patients, 176 (56.4%) were diagnosed with non‐alcoholic steatohepatitis. During a median follow‐up period of 4.8 years (range, 0.3–15.8), six patients (1.9%) developed HCC, and 20 (6.4%) developed extrahepatic cancer. Multivariate analysis identified fibrosis stage (≥3; hazard ratio [HR], 12.3; 95% confidence interval [CI], 1.11–136.0; P = 0.041) as a predictor for HCC and type IV collagen 7s (>5 ng/mL; HR, 1.74; 95% CI, 1.08–2.79; P = 0.022) as a predictor for extrahepatic cancer. Eight patients (2.6%) died during the follow‐up period. The most common cause of death was extrahepatic malignancy. None died of cardiovascular disease. Multivariate analysis identified type IV collagen 7s (>5 ng/mL; HR, 3.38; 95% CI, 1.17–9.76; P = 0.024) as a predictor for mortality. Conclusion The incidence of extrahepatic cancer was higher than that of HCC. Severe fibrosis was a predictor for HCC. Patients with NAFLD and elevated type IV collagen 7s levels are at increased risk for extrahepatic cancer and overall mortality.